Asymmetric alkylations using SuperQuat auxiliaries - an investigation into the synthesis and stability of enolates derived from 5,5-disubstituted oxazolidin-2-ones - Bull, S; Davies, S; Jones, S; Sanganee, H (1999)
Studies on the alkylation of enolates derived from a range of W-acyl-5,5-dimethyloxazolidin-2-ones and N-acyl-5,5diphenyloxazolidin-2-ones reveal that high yields and high diastereoselectivities are best obtained when homochiral 4-isopropyl-5,5-dimethyIoxazolidin-2-one is employed as a chiral auxiliary.